2018
DOI: 10.1128/aem.02322-17
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Mineral-Bound Iron to a Snow Algal-Bacterial Coculture and Implications for Albedo-Altering Snow Algal Blooms

Abstract: Snow algae can form large-scale blooms across the snowpack surface and near-surface environments. These pigmented blooms can decrease snow albedo, increase local melt rates, and may impact the global heat budget and water cycle. Yet, underlying causes for the geospatial occurrence of these blooms remain unconstrained. One possible factor contributing to snow algae blooms is the presence of mineral dust as a micronutrient source. We investigated the bioavailability of iron (Fe) -bearing minerals, including fors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…Fe, a key micronutrient for photosynthetic growth, is necessary to support the formation of high‐density snow algal blooms (Harrold et al. ). Using Fe 90 in Chloromonas brevispina ‐bacterial coculture experiments, snow algal growth was stimulated.…”
Section: Diversity and Community Structurementioning
confidence: 99%
“…Fe, a key micronutrient for photosynthetic growth, is necessary to support the formation of high‐density snow algal blooms (Harrold et al. ). Using Fe 90 in Chloromonas brevispina ‐bacterial coculture experiments, snow algal growth was stimulated.…”
Section: Diversity and Community Structurementioning
confidence: 99%
“…isolated from snow grew better in the presence of bacteria from a field sample than when plated with an antibiotic. Another study, co-culturing snow bacteria and Chloromonas brevispina, showed increased iron containing mineral dissolution, which stimulated algae growth, suggesting bacteria could help snow algae obtain bioavailable iron from mineral dust (Harrold et al, 2018). Although little data exist for algae-fungal mutualisms outside of lichens, metabolite exchange can occur between yeast (Saccharomyces cerevisiae) and microalgae (Chlamydomonas reinhardtii; Hom and Murray, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bacteria and fungi may increase ecosystem carrying capacity, and thus the abundance of algae and algal BAR, through the liberation of phosphorus (P) and Fe (and other micronutrients) from rock flour and surface debris, while producing labile organic C that is readily consumed by heterotrophs through photosynthesis (Kellerman et al, 2020;Musilova et al, 2016). Experimental evidence supports this thesis; bacteria enhance the growth rate and abundance of snow algae in the presence of Fe-bearing minerals (Harrold et al, 2018;Lutz et al, 2015;Phillips-Lander et al, 2020). Viruses have not been directly linked to BAR but they may play an indirect role by regulating bacterial mortality, thereby influencing levels of dissolved organic matter (Anesio et al, 2007;Bellas et al, 2013).…”
Section: Surface Microbesmentioning
confidence: 95%
“…Snow and ice algae are water-limited and potentially nutrient-limited (Anesio et al, 2017;Ganey et al, 2017;Havig, 2017, 2020;Lutz et al, 2015;Takeuchi et al, 2006). Algae and other psychrophilic microorganisms are also known to interact in their use of several limiting resources [e.g., C, iron (Fe), and N (Anesio et al, 2017;Harrold et al, 2018;Havig and Hamilton, 2019;Hodson et al, 2008;Phillips-Lander et al, 2020;Stibal et al, 2009;Telling et al, , 2011]. Therefore, bacteria and fungi may increase ecosystem carrying capacity, and thus the abundance of algae and algal BAR, through the liberation of phosphorus (P) and Fe (and other micronutrients) from rock flour and surface debris, while producing labile organic C that is readily consumed by heterotrophs through photosynthesis (Kellerman et al, 2020;Musilova et al, 2016).…”
Section: Surface Microbesmentioning
confidence: 99%